The expanding horizon of alkyl quinolone signalling and communication in polycellular interactomes - Reen, F.; McGlacken, G.; O'Gara, Fergal (Oxford University Press, 2018)
Population dynamics within natural ecosystems is underpinned by microbial diversity and the heterogeneity of host-microbe and microbe-microbe interactions. Small molecule signals that intersperse between species have been shown to govern many virulence-related processes in established and emerging pathogens. Understanding the capacity of microbes to decode diverse languages and adapt to the presence of 'non-self' cells will provide an important new direction to the understanding of the 'polycellular' interactome. Alkyl quinolones (AQs) have been described in the ESKAPE pathogen Pseudomonas aeruginosa, the primary agent associated with mortality in patients with cystic fibrosis and the third most prevalent nosocomial pathogen worldwide. The role of these molecules in governing the physiology and virulence of P. aeruginosa and other pathogens has received considerable attention, while a role in interspecies and interkingdom communication has recently emerged. Herein we discuss recent advances in our understanding of AQ signalling and communication in the context of microbe-microbe and microbe-host interactions. The integrated knowledge from these systems-based investigations will facilitate the development of new therapeutics based on the AQ framework that serves to disarm the pathogenesis of P. aeruginosa and competing pathogens.